Offer and demand of therapeutic equivalence studies (in vitro and in vivo) for medicines in Costa Rica - Pereira-Vega, Zacarías (2016)
In the last decades the constant increase of medicine expenses worldwide, as well as the population growth and the increase of life expectancy, has led governments to look for alternatives to help reduce the impact of this matter in their budgets. Generic medicines are one option because they are cheaper than originator medicines. Nevertheless, the generic medicine must prove its therapeutic equivalence, before its registration, by undergoing in vitro and/or in vivo essays compared to a reference medicine to guarantee its quality, safety and efficacy; and, thus, its interchangeability. An on line survey executed in March and April, 2013, helped determine there was a demand for 85 medicines produced in Costa Rica that, to be registered in the country, required the same amount of therapeutic equivalence studies; 47 required in vitro essays and 38 required in vivo essays. This demand came mainly from four laboratories that produce medicines in the country; it increases if exported medicines are included. Regarding the national offer of these services (in vitro and in vivo essays) from laboratories that do not belong to the producer, it is well known that this is very limited, since there were only two laboratories offering the service, and their work is limited, for now, to in vitro essays.